Case Study to Analyze the Impact of Multi-Course Project-Based Learning Approach on Education for Sustainable Development - Amith Khandakar (14151981) (2020)
This work presents a multi-course project-based learning (MPL) approach implemented using two electrical engineering (EE) interdisciplinary undergraduate courses at Qatar University. Implementing an MPL approach helps in the development of critical thinking and collaborative decision-making skills. The attainment of these skills is also the outcome of education for sustainable development (ESD); the skills help students acquire the knowledge, attitudes, and values necessary to shape a sustainable future. The participating students’ worked on a design project, which was used to assess the fulfillment of a set of student learning outcomes (SLOs), focusing on engineering soft skills and project management skills. The skills include the ability to communicate effectively, to work collaboratively in a team, to think both critically and creatively, and to manage projects efficiently with realistic constraints and standards. The challenges of implementing the MPL method are the organization of pedagogical activities that are planned for each of the courses involved, the coordination of the materials delivered by each course, and the supervision of around 90 students per year performing the MPL method. The experience of MPL deployment in the EE program was rated using student surveys. It was assumed that the MPL approach would be beneficial to the students based on the instructors’ and students’ feedback from the same courses in previous years. This was verified using chi-square statistics of the survey results. The implementation of the MPL also helped in increasing the average marks scored by the students in the design project. Some interesting feedback, statistical analyses, and improvement actions are reported for future upgrades. This work also contributes to the MPL pragmatic body of knowledge by exploring a successful initiative and its outcomes, which can help in attaining the skills needed for ESD. Other Information Published in: Sustainability License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.3390/su12020480